Designing A Reverse Logistics Monitoring System for Logistics Products at PT XYZ - Purbanuara Parlindungan Sitorus; Sita Anlisah Sholihah; Havid Lucky Fadzrin (Publikasi Indonesia, 2025)
The process of product returns from suppliers is very urgent to reduce large company losses due to products returned from suppliers experiencing many problems. This study aims to measure the supply chain performance in each backflow supply chain of telecommunication industry products in Indonesia. Analysis was conducted using the SCOR model and determination of value weighting using AHP. The results of the analysis with 10 indicators for the delivery and return process show that the total value of PT. XYZ's company performance is still far from the target. This indicator must be corrected because there is a need for an increase in company performance, namely the Delivery and Return indicators, one of which occurs in returns when the driver brings damaged goods taken from the supplier and repackages, or commonly called repackaging, the damaged product in the PT. XYZ warehouse. There is a shortage[A1] [A2] or lagging of some of these products. The results of the analysis also show that PT. XYZ has the lowest performance value on both criteria, namely delivery and return, where each of these values can be categorized as